Sediment characterization by echosounding and sampling - Kuhn, Gerhard; Brückner, Sylvia; Didik, Claudia; Forwick, Matthias; Hass, Christian; Lensch, Norbert; Schmitt, Wolfgang; Waldthausen, Constanze V; Wittling, Thomas (The Expedition ANTARKTIS-XX of RV Polarstern in 2002/2003 Reports of Legs 1 and 2, 2005)
The reconstruction of the paleoclimatic and paleoceanographic development of the late Quaternary Southern Ocean and adjacent continental areas in high temporal and spatial resolution is a main goal of our longterm study. During ANT-XX/2 the sedimentary budget of biogenic and terrigenous components and their variability was investigated in cooperation with geochemical projects. Main objectives were the relationships between production of biogenic components and input of terrigenous components and involved nutrients.
Keywords: Sørishavet; geokjemi; marin geologi; oseanografi; paleoklimatologi

Characteristics of Weddell Sea Shelf sediments obtained by diamond core drilling, Antarctica - Strand, Kari; Kristoffersen, Yngve (FINNARP -95/96: Weddel Sea Joint Nordic Expedition, 1997)
Keywords: Sørishavet; geokjemi; sedimenter

Chemical weathering in permafrost regions of Antarctica: Great Wall Station of China, Casey Station and Davis Station of Australia - Xie, Youyu (Proceedings / Permafrost, Fifth International Conference, 1988)
Keywords: Antarktis; geofysikk; geokjemi

Age relationships of Mesozoic basalt lava and dykes in Vestfjella, Dronning Maud Land, Antarctica - Furnes, Harald; Mitchell, John G (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geokjemi; geologi; petrografi; vulkaner